PERANCANGAN SISTEM INFORMASI DATA NILAI SISWA DI SMAN 2 PADANG BOLAK SUMATERA UTARA MENGGUNAKAN METODE PROTOTYPING - Eko Martantoh; Juni Asmidar Harahap (Journal of Innovation And Future Technology (IFTECH), 2023)
This study aims to design and implement an information system for student grade data at SMAN 2 Padang Bolak, North Sumatra. The method used is classroom action research using a prototyping model. The increase in the number of students and the complexity of managing data on student scores has made schools need an information system that is able to manage data more efficiently and effectively. The results showed that the designed student grade data information system could improve efficiency in managing student grade data and make it easier for schools to see student academic progress. The benefits of this research are to assist schools in managing student grade data more easily and effectively and to improve the quality of education at SMAN 2 Padang Bolak, North Sumatra. In conclusion, this study succeeded in designing and implementing a student grade data information system at SMAN 2 Padang Bolak, North Sumatra using the prototyping method which is capable of increasing the efficiency and effectiveness of managing student grade data. It is hoped that the results of this research can make a positive contribution to the school and community in the field of education.